Cancer-Induced Reprogramming of Host Glucose Metabolism: “Vicious Cycle” Supporting Cancer Progression - Schwartsburd, Polina (Frontiers in Oncology, 2019)
Unrestricted cancer growth requires permanent supply of glucose that can be obtained from cancer-mediated reprogramming of glucose metabolism in the cancer-bearing host. The pathological mechanisms by which cancer cells exert their negative influence on host glucose metabolism are largely unknown. This paper proposes a mechanism of metabolic and hormonal changes that may favor glucose delivery to tumor (not host) cells by creating a cancer-host «vicious cycle» whose prolonged action drives cancer progression and promotes host cachexia. To verify this hypothesis, a feedback model of host-cancer interactions that create the «vicious cycle» via cancer-induced reprogramming of host glucose metabolism is proposed. This model is capable of answering some crucial questions as to how anabolic cancer cells can reprogram the systemic glucose metabolism and why these pathways were not observed in pregnancy. The current paper can also explain the pathogenesis of cancer progression and identify hormonal/metabolic targets for anti-cancer treatment.